Andrew Gilbert - Ulundi is Jerusalem, Andrew is emperor, brocoli is holy - Zybok, Oliver 1972- (Kerber art, 2017)
In his works on paper and large-scale installations, the Scottish artist Andrew Gilbert combines fictive situations with historical fact. The impulse is always provided by incidents connected with colonialism, especially that of the British Empire, which in the way he reflects on them, go far beyond the historical context, and whose consequences still weigh heavily until today. His work also examines the reappraisal of that time in films and literature. His method is reincarnation. Through slipping into the role of a British major or general, assimilating alien identities, and appearing as a real or fictive character in his artistic work, he succeeds in projecting history into the present (Zdenek Felix). Visions of the past and its impact on the present remain palpable. Within this context, the Berlin-based artist examines the repercussions of historical facts in art, in particular the Expressionists and their handling of so-called Primitivism. Exhibition: Overbeck-Gesellschaft / St. Petri - Lübeck, Germany (28.02-17.04.2016)